Correction to the Number of Homomorphisms From Quaternion Group into Some Finite Groups - Bo Shang; Jinke Hai (International Journal of Mathematics And its Applications, 2016)
Using only elementary group theory, we determine the number of homomorphisms from quaternion group into some finite groups.